Preschool Educational Institutions and Family Partnership - Bakhtiyor Umidovich Aminov; Yoqutkhon Mirzakarim kizi Xolikova (International Journal on Integrated Education, 2022)
The family and the preschool educational organization are two active components of the cooperation system, but the problem of their interaction has recently become one of the most urgent. The family is one of the greatest values created by mankind in the entire history of its existence. Not a single nation, not a single cultural community has managed - and does not do - without a family. Society and the state are interested in its positive development and preservation; every person needs a strong, reliable family.